Assessment of the phytotoxic, cytogenotoxic, antibacterial and antibiofilm properties of Salvia sclarea essential oil - I. Mahmutović-Dizdarević; A. Mesic; M. Avdić; A. Borić; S. Husić; R. Klasan; A. Parić (Regulatory Mechanisms in Biosystems, 2025)
Synthetic herbicides have adverse effects on the environment and human health. Understanding allelopathic intera c tions can provide alternatives for weed control without using these synthetic chemicals. This study investigated the impact of three concentrations (10, 20, and 30 μg/m L ) of Salvia sclarea essential oil (EO) on the Matricaria chamomilla , Leuca n themum vulgare , and Trifolium repens germination process, as well as its toxicological and antimicrobi al profile. Our results showed that S. sclarea EO, particularly at higher concentrations, affected the germination and growth parameters of the tested species, with T. repens being the most sensitive. A statistically significant increase in the value of the mitotic index was observed for all three tested concentrations of S. sclarea EO compared to the control group. A significant i n crease in the number of acentric fragments at between 10 and 30 µg/m L of S. sclarea EO compared to the control group, as well as an increase in the frequency of aneuploidy at between 10 µg/m L of S. sclarea EO compared to the control was detected. Minimum inhibitory concentration of EO was 500 μ L /m L for all tested bacteria. Impact on the bacterial biofilm formation was species-specific and concentration dependent. Our findings suggest that S. sclarea EO possesses certain allelopathic, proliferative, genotoxic, and antibacterial potential.